The effect of benefits on single motherhood in Europe - Libertad González (Institute for the Study of Labor (IZA), 2006)
This paper uses data from the eight waves of the European Community Household Panel (1994-2001) to estimate the impact of welfare benefits on the incidence of single motherhood and headship among young women across European countries. The regressions include country fixed effects as well as time trends that are allowed to vary by country, to account for fixed and trending unmeasured factors that could influence both benefit levels and family formation. The analysis also accounts for individual characteristics and labor market conditions. The results suggest that benefit levels have a small but significant positive effect on the prevalence of single mothers. An increase in yearly benefits of 1,000 euros is estimated to increase the incidence of single mother families by about 2 percent.
Keywords: J12; J13; I38; 330; single mothers; welfare benefits; Alleinerziehende; Familienleistungsausgleich; EU-Staaten